2021
DOI: 10.1007/s00170-021-07633-y
|View full text |Cite
|
Sign up to set email alerts
|

Study of dieless radial spinning for thick-walled cylindrical parts with external grooves

Abstract: Thick-walled cylindrical parts with external grooves are common components in the automobile and aviation fields. Such components can be produced by pressing the outer surface of a spinning thick-walled aluminum alloy tube by the dieless radial spinning process. The forming characteristics in the spinning process and the effects of various process parameters on forming were studied by using orthogonal tests and finite element simulations. During the forming process, bulge and thickness reductions occur because… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Three spinning methods were contrasted in their study to control thickness distribution and suppress the wrinkling defect. Liu et al [17] produced the thick-wall cylindrical part with external grooves using double rollers. Kwiatkowski et al [18] compared different roller trajectories for spinning necking tube without any mandrel and concluded that the value of inclined area as well as the elongation of the part highly depend on the roller path.…”
Section: Introductionmentioning
confidence: 99%
“…Three spinning methods were contrasted in their study to control thickness distribution and suppress the wrinkling defect. Liu et al [17] produced the thick-wall cylindrical part with external grooves using double rollers. Kwiatkowski et al [18] compared different roller trajectories for spinning necking tube without any mandrel and concluded that the value of inclined area as well as the elongation of the part highly depend on the roller path.…”
Section: Introductionmentioning
confidence: 99%